KEGIATAN LIVE IN DALAM MENGEMBANGKAN RASA EMPATI SISWA - Fajar Selawati; Yasnita; Tjipto Sumadi (Jurnal Ilmiah Mimbar Demokrasi, 2019)
The aim of this research is to knowing about Live In Program to Improving of Student‟s Empathy in SMP Kolese Kanisius Jakarta. This research use a qualitative method began at observation, documentation, and also interview to students grade VIII (Eight) as an informan and vice principal as a key informan. SMP Kolese Kanisius Jakarta‟s Live In Program is implement by placing students in a village and living with host family for seven days. During that time, students directly feel the life with villagers by following host family‟s daily activities. Those activities include farming, selling, gardening, raising, and others daily activities. The result shows that trough live in program, students have a chance to improve and sharpened their empathy towards others. In addition, this program also will increase student‟s independence.